Computational modeling of superparamagnetic nanoparticle-based (affinity) diagnostics - Van Dieren, Loïc; Tereshenko, Vlad; Oubari, Haïzam; Berkane, Yanis; Cornacchini, Jonathan; Thiessen EF, Filip; Cetrulo, Curtis L.; Uygun, Korkut; Lellouch, Alexandre G. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction Magnetic nanoparticles (MNPs), particularly iron oxide nanoparticles (IONPs), are renowned for their superparamagnetic behavior, allowing precise control under external magnetic fields. This characteristic makes them ideal for biomedical applications, including diagnostics and drug delivery. Superparamagnetic IONPs, which exhibit magnetization only in the presence of an external field, can be functionalized with ligands for targeted affinity diagnostics. This study presents a computational model to explore the induced voltage in a search coil when MNPs pass through a simulated blood vessel, aiming to improve non-invasive diagnostic methods for disease detection and monitoring. Methods A finite element model was constructed using COMSOL Multiphysics to simulate the behavior of IONPs within a dynamic blood vessel environment. Governing equations such as Ampère’s law and Faraday’s law of induction were incorporated to simulate the induced voltage in a copper coil as MNPs of various sizes flowed through the vessel. Rheological parameters, including blood viscosity and flow rates, were factored into the model using a non-Newtonian fluid approach. Results The amount of MNPs required for detection varies significantly based on the sensitivity of the detection equipment and the size of the nanoparticles themselves. For highly sensitive devices like a SQUID voltmeter, with a coil sensitivity approximately 10−12 V, very low MNP concentrations—approximately 10−4 μg/mL—are sufficient for detection, staying well within the safe range. As coil sensitivity decreases, such as with standard voltmeters at 10−8 V or 10−6 V, the MNP concentration required for detection rises, approaching or even exceeding potentially toxic levels. Additionally, the physical size of MNPs plays a role; larger nanoparticles (e.g., 50 nm radius) require fewer total particles for detection at the same sensitivity than smaller particles like those with a 2.5 nm radius. For instance, at a coil sensitivity of 10−10 V, a 2.5 nm particle requires approximately 1012 particles, whereas a 50-nm particle only needs 108. This highlights the importance of optimizing both detection sensitivity and particle size to balance effective detection with safety. Conclusion This computational model demonstrates the feasibility of using superparamagnetic nanoparticles in real-time, non-invasive diagnostic systems.